2021
DOI: 10.3390/microorganisms9061158
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Antimycobacterial Mechanism of Action of Ciprofloxacin Using Metabolomics

Abstract: In the interest of developing more effective and safer anti-tuberculosis drugs, we used a GCxGC-TOF-MS metabolomics research approach to investigate and compare the metabolic profiles of Mtb in the presence and absence of ciprofloxacin. The metabolites that best describe the differences between the compared groups were identified as markers characterizing the changes induced by ciprofloxacin. Malic acid was ranked as the most significantly altered metabolite marker induced by ciprofloxacin, indicative of an in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 156 publications
(141 reference statements)
0
10
0
Order By: Relevance
“…It has also been demonstrated that ciprofloxacin, in addition to its effect on DNA gyrase, can cause reduction in the amount of DNA, RNA, and protein, as well as phospholipids, galactose, arabinose, glucosamine, and the mycolic acid of the M. smegmatis cell wall. However, these findings should be confirmed in the further studies (Figure 2) (11). Ciprofloxacin affects several Gram-positive bacteria such as Staphylococcus, Streptococcus, Enterococcus, Bacillus spp., and Mycobacterium.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 84%
“…It has also been demonstrated that ciprofloxacin, in addition to its effect on DNA gyrase, can cause reduction in the amount of DNA, RNA, and protein, as well as phospholipids, galactose, arabinose, glucosamine, and the mycolic acid of the M. smegmatis cell wall. However, these findings should be confirmed in the further studies (Figure 2) (11). Ciprofloxacin affects several Gram-positive bacteria such as Staphylococcus, Streptococcus, Enterococcus, Bacillus spp., and Mycobacterium.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 84%
“…Similarly, the induction of the SOS response and growth arrest were observed in P. aeruginosa treated with 0.12 mg/L CIP for 5 days; notably, the SOS response can lead to a 10- to 100-fold increase in persister cell levels. ,, In summary, P CIP cells developed CIP resistance by adopting various physiological strategies. Instantaneous targeted mutations (i.e., DNA gyrase) are possible and may play a role in CIP resistance.…”
Section: Results and Discussionmentioning
confidence: 75%
“…Similarly, the induction of the SOS response and growth arrest were observed in P. aeruginosa treated with 0.12 mg/L CIP for 5 days; notably, the SOS response can lead to a 10-to 100-fold increase in persister cell levels. 19,22,23 Interestingly, the traits of P CIP/Ag + cells were similar to those of P CIP cells, and the selection mechanisms were the same because the bacteria developed similar detoxification mechanisms upon Ag + and CIP exposure. For example, bacteria undergoing anaerobic respiration utilize Ag + as terminal electron acceptors, thus reducing it to the particulate form, which diminishes its bioavailability and toxicity.…”
Section: Resultsmentioning
confidence: 93%
“…It is worth noting that in C. acnes treated with EO, the abundance of these two unsaturated fatty acids 9-Octadecenoic acid and (9Z)-Hexadecenoic acid, main components of the cell wall and cell membrane, increased significantly, indicating that the synthesis and repair of the cell wall and cell membrane were strongly up-regulated ( Supplementary File 3 ). It has been shown in the literature that microorganisms would protect themselves by the increase of unsaturated fatty acids to avoid damage caused by the administration, which was a stress response ( Knoll et al, 2021 ). Therefore, it could be suggested that the damage of the EO to the cell wall and the cell membrane of the C. acnes may be indirectly caused by the influence of metabolism.…”
Section: Discussionmentioning
confidence: 99%